Water-based UV coating and preparation method thereof

By using modified polyurethane acrylate and modified nanocellulose in aqueous UV coatings, the problem of traditional aqueous UV coatings is easily breeding mold and poor water resistance, and the coating film has achieved high antibacterial properties, water resistance and adhesion.

CN119842271APending Publication Date: 2025-04-18ZHEJIANG ANYI NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411879387.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Traditional water-based UV coatings are prone to mold growth during film formation and have poor water resistance, resulting in reduced service life and shedding of the coating.

Method used

Acrylic resin and modified polyurethane acrylate are used as the main matrix, and functional additives such as modified nanocellulose are added. By synergistically acting in the quaternary ammonium structure in the modified polyurethane acrylate and the fluorine element in the polysiloxane, the antibacteriality, water resistance and adhesion of the coating film are improved.

Benefits of technology

It significantly improves the overall performance of the coating, including antibacterial properties, water resistance and adhesion, extends the service life of the coating and reduces shedding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, and discloses a water-based UV coating and a preparation method thereof. According to the prepared water-based UV coating, the acrylic resin serves as a main matrix, and functional auxiliaries such as the modified polyurethane acrylate and the modified nanocellulose are added, so that the comprehensive performance of a coating film is improved; wherein due to the introduction of the modified polyurethane acrylate, the antibacterial property, the water resistance and the adhesive force of a coating film are improved; and due to the introduction of the modified nano cellulose, the paint film property, durability and the like of a coating film are improved. Therefore, the prepared water-based UV coating can be widely applied to related products of home decoration, medical treatment, sanitation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a water-based UV coating and a preparation method thereof. Background Art

[0002] Waterborne UV coatings are composed of oligomers, active diluents, photoinitiators and other functional additives, and have the advantages of fast curing speed, energy saving and low VOC emissions. Therefore, they are widely used in indoor furniture coatings, interior wall coatings, 3C electronic product coatings and automotive interior coatings. Waterborne UV coatings are mainly classified into acrylic resins, unsaturated polyesters, polyether acrylates, epoxy acrylates, polyurethane acrylates, etc. according to the base resin. Among them, polyurethane acrylates have the advantages of good wear resistance, strong toughness, strong adjustability, good overall performance and good adhesion. Using it together with acrylic resin as the main base resin has the effect of improving the comprehensive performance of the coating.

[0003] Although traditional water-based UV coatings have many advantages, they also have some disadvantages that need to be modified. For example: (1) Water-based coatings are easily affected by environmental factors during film formation and are prone to mold growth, which can reduce the service life of the cured coating. (2) Water-based coatings generally have poor water resistance, which can cause the coating surface to peel off, fold, and crack after being eroded by water molecules, thus limiting the application of water-based coatings in many fields. Therefore, in view of the shortcomings of water-based UV coatings, researchers need to develop a coating with excellent comprehensive properties such as good wear resistance, strong adhesion, good antibacterial properties, and good water resistance to meet practical application needs. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a water-based UV coating and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A water-based UV coating comprises the following raw materials in parts by weight: 35-45 parts of acrylic resin, 20-30 parts of modified polyurethane acrylate, 1-3 parts of modified nanocellulose, 4-6 parts of photoinitiator, 0.1-0.5 parts of defoamer, 0.3-0.5 parts of leveling agent, and 15-25 parts of deionized water; The photoinitiator is photoinitiator TPO, the defoamer is Tego810 defoamer, and the leveling agent is diacetone alcohol; The modified polyurethane acrylate is prepared by the following steps: Step A1, 1,3-dibromopropane and sodium hydroxide are uniformly dispersed in N,N-dimethylformamide (DMF), and then diethanolamine is added, and the mixture is stirred at room temperature for 24 hours, and purified to obtain an intermediate; Step A2, dispersing epichlorohydrin in methanol, transferring to an oil bath, and heating to 60-70° C., then slowly adding the intermediate and stirring to react for 5-7 hours, cooling to room temperature, and distilling and washing under reduced pressure to obtain a functional monomer; Step A3, mixing the vacuum dried and dehydrated polyethylene adipate (molecular weight of 1000) and 80% dibutyltin dilaurate, stirring for 10 minutes at 50-60° C. under nitrogen, slowly adding isophorone diisocyanate and stirring for 30-60 minutes, then heating to 75-85° C., adding a functional monomer DMF solution, stirring for 1.5-2.5 hours, then adding a 2,2-dihydroxymethylpropionic acid DMF solution and reacting for 3-4 hours, then cooling to 70° C., adding the remaining 20% ​​dibutyltin dilaurate and p-methylphenol, stirring for 10-30 minutes, then adding polysiloxane and stirring for 4-6 hours, then cooling to 45-55° C., adding triethylamine and deionized water, and stirring at a speed of 1000-1500 rpm for 20 minutes to obtain modified polyurethane acrylate; Further, in step A1, the usage ratio of 1,3-dibromopropane, sodium hydroxide, N,N-dimethylformamide and diethanolamine is 0.01-0.02 mol: 1.25-2.5 g: 100 mL: 0.034-0.068 mol; Further, in step A2, the usage ratio of epichlorohydrin, methanol and intermediate is 0.01-0.03 mol:100 mL:5.25-15.5 g; Further, in step A3, the dosage ratio of polyethylene adipate, dibutyltin dilaurate, isophorone diisocyanate, functional monomer DMF solution, 2,2-dihydroxymethylpropionic acid DMF solution, p-methylphenol, polysiloxane, triethylamine and deionized water is 0.02-0.03 mol: 0.003-0.006 g: 0.05-0.07 mol: 10 mL: 10 mL: 0.0001-0.0003 g: 3-6 g: 0.01-0.26 mol: 5-10 mL; Furthermore, in step A3, the functional monomer DMF solution is prepared by mixing and stirring the functional monomer and DMF in a dosage ratio of 2-4 g:10 mL, and the 2,2-dihydroxymethylpropionic acid DMF solution is prepared by mixing and stirring 2,2-dihydroxymethylpropionic acid and DMF in a dosage ratio of 1.5-2.5 g:10 mL; Furthermore, in step A3, the polysiloxane is synthesized by the following steps: trifluoropropane trimethoxysilane, dimethyl dimethoxysilane, diphenylsilane diol, pentaerythritol triacrylate and barium hydroxide are mixed and stirred uniformly, and nitrogen is continuously introduced, the temperature is raised to 75-85° C., the reaction is carried out for 5-6 hours, and vacuum drying is performed to obtain polysiloxane; Furthermore, in the step A3 polysiloxane, the usage ratio of trifluoropropane trimethoxysilane, dimethyl dimethoxysilane, diphenylsilane diol, pentaerythritol triacrylate and barium hydroxide is 0.001-0.005 mol: 0.005-0.01 mol: 0.001-0.003 mol: 0.001-0.002 mol: 0.04-0.07 g.

[0006] The modified nanocellulose is prepared by the following steps: grinding the nanocellulose for 1-3 hours, adding DMF and stirring evenly, adding 4-bromo-1-butene and sodium hydroxide, stirring and reacting for 15-20 hours, centrifuging and purifying to obtain the modified nanocellulose; Furthermore, the usage ratio of nanocellulose, DMF, 4-bromo-1-butene and sodium hydroxide in the modified nanocellulose is 1-3 g: 50 mL: 3-4 g: 1.5-3.5 g.

[0007] A method for preparing a water-based UV coating comprises the following steps: Weigh the raw materials by weight, mix the acrylic resin, modified polyurethane acrylate and deionized water, stir and mix them evenly, then add the modified nanocellulose, photoinitiator, defoamer and leveling agent, stir and mix for 10-20 minutes, and then ultrasonically treat for 30 minutes to obtain the water-based UV coating.

[0008] Beneficial effects of the present invention: The water-based UV coating prepared by the present invention is based on acrylic resin as the main matrix, and functional additives such as modified polyurethane acrylate and modified nanocellulose are added to improve the comprehensive performance of the coating film; wherein, the introduction of modified polyurethane acrylate improves the antibacterial property, water resistance and adhesion of the coating film; the introduction of modified nanocellulose improves the film properties and durability of the coating film. Therefore, the water-based UV coating prepared by the present invention can be widely used in home decoration, medical treatment, sanitation and other related products.

[0009] In the modified polyurethane acrylate, the -Br group in 1,3-dibromopropane and the -NH- group in diethanolamine are reacted to obtain an intermediate; then the -Cl group in epichlorohydrin is reacted with the primary amine in the intermediate to obtain a functional monomer containing a hydroxyl group, an epoxy group and a quaternary ammonium salt structure; then trifluoropropane trimethoxysilane, dimethyldimethoxysilane, diphenylsilanediol and pentaerythritol triacrylate are used as raw materials to synthesize a polysiloxane containing a hydroxyl group, a fluorine atom and a terminal double bond structure; finally, polyethylene adipate, isophorone diisocyanate, a functional monomer, 2,2-dihydroxymethylpropionic acid and polysiloxane are used as raw materials to synthesize the modified polyurethane acrylate. Modified polyurethane acrylate not only has the wear resistance and flexibility of polyurethane, but also has the excellent adhesion and environmental protection of acrylate. Introducing it into the matrix can significantly improve the comprehensive performance of the base coating. Among them, the introduction of quaternary ammonium salt structure makes the coating film have excellent antibacterial properties, which can effectively reduce the phenomenon of mold breeding in the film-forming process of water-based coatings. The introduction of silicone structure and fluorine element can work synergistically to make the coating film stable in a humid environment, not easily eroded by water, and improve the water resistance of the coating film. In addition, modified polyurethane acrylate also contains multiple double bond structures, which can participate in the curing of the coating. After curing, a dense and uniform cross-linked network is formed, making it difficult for water molecules to enter the interior of the coating film, further improving the water resistance of the matrix. At the same time, the active group epoxy group it contains can also react with the active groups on the surface of the substrate to form chemical bonds, further improving the adhesion of the coating film.

[0010] The modified nanocellulose is surface treated with 4-bromo-1-butene to provide a carbon-carbon double bond structure on its surface that can participate in curing, thereby increasing the cross-linking density of the coating. The high aspect ratio and high strength of nanocellulose are also used to improve the paint film properties of the coating, thereby increasing the wear resistance and durability of the film layer. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0012] Example 1: Polysiloxane is synthesized by the following steps: 0.001 mol of trifluoropropane trimethoxysilane, 0.005 mol of dimethyldimethoxysilane, 0.001 mol of diphenylsilanediol, 0.001 mol of pentaerythritol triacrylate and 0.04 g of barium hydroxide are mixed and stirred evenly, and nitrogen is continuously introduced, the temperature is raised to 75°C for reaction for 5 hours, and vacuum dried to obtain polysiloxane.

[0013] The modified polyurethane acrylate is prepared by the following steps: Step A1, 0.01 mol 1,3-dibromopropane and 1.25 g sodium hydroxide were evenly dispersed in 100 mL N,N-dimethylformamide (DMF), and then 0.034 mol diethanolamine was added, and the mixture was stirred at room temperature for 24 hours, and purified to obtain an intermediate; Step A2, disperse 0.01 mol of epichlorohydrin in 100 mL of methanol, transfer to an oil bath, and heat to 60° C., then slowly add 5.25 g of the intermediate and stir to react for 5 h, cool to room temperature, distill under reduced pressure, and wash to obtain a functional monomer; Step A3: Mix 0.02 mol polyethylene adipate (molecular weight 1000) and 0.0024 g dibutyltin dilaurate after vacuum drying and dehydration, stir for 10 min at 50 °C under nitrogen, slowly add 0.05 mol isophorone diisocyanate and stir for 30 min, then heat to 75 °C, add 10 mL functional monomer DMF solution, stir for 1.5 h, and then add 10 mL The 2,2-dihydroxymethylpropionic acid DMF solution was reacted for 3 hours, then cooled to 70°C, the remaining 0.0006g of dibutyltin dilaurate and 0.0001g of p-methylphenol were added, stirred for 10 minutes, and then 3g of polysiloxane was added and stirred for 4 hours, then cooled to 45°C, 0.01mol of triethylamine and 5mL of deionized water were added, and stirred at a speed of 1000rpm for 20 minutes to obtain modified polyurethane acrylate. The functional monomer DMF solution was prepared by mixing and stirring the functional monomer and DMF in a dosage ratio of 2g:10mL, and the 2,2-dihydroxymethylpropionic acid DMF solution was prepared by mixing and stirring 2,2-dihydroxymethylpropionic acid and DMF in a dosage ratio of 1.5g:10mL.

[0014] The modified nanocellulose is prepared by the following steps: 1 g of nanocellulose was ground for 1 h, and then 50 mL of DMF was added and mixed evenly, 3 g of 4-bromo-1-butene and 1.5 g of sodium hydroxide were added, and the mixture was stirred for 15 h. The mixture was centrifuged and purified to obtain modified nanocellulose.

[0015] Example 2: Polysiloxane is synthesized by the following steps: 0.003 mol of trifluoropropane trimethoxysilane, 0.0075 mol of dimethyldimethoxysilane, 0.002 mol of diphenylsilanediol, 0.0015 mol of pentaerythritol triacrylate and 0.055 g of barium hydroxide are mixed and stirred evenly, and nitrogen is continuously introduced, the temperature is raised to 75-85°C, the reaction is carried out for 5.5 hours, and vacuum drying is performed to obtain polysiloxane.

[0016] The modified polyurethane acrylate is prepared by the following steps: Step A1, 0.015 mol 1,3-dibromopropane and 1.88 g sodium hydroxide were evenly dispersed in 100 mL N,N-dimethylformamide (DMF), and then 0.051 mol diethanolamine was added, and the mixture was stirred at room temperature for 24 hours, and purified to obtain an intermediate; Step A2, disperse 0.02 mol of epichlorohydrin in 100 mL of methanol, transfer to an oil bath, and heat to 65° C., then slowly add 10.5 g of the intermediate and stir to react for 6 h, cool to room temperature, distill under reduced pressure, and wash to obtain a functional monomer; Step A3: Mix 0.025 mol polyethylene adipate (molecular weight 1000) and 0.0036 g dibutyltin dilaurate after vacuum drying and dehydration, stir for 10 min at 55 °C under nitrogen, slowly add 0.06 mol isophorone diisocyanate and stir for 45 min, then heat to 80 °C, add 10 mL functional monomer DMF solution, stir for 2 h, and then add 10 mL The 2,2-dihydroxymethylpropionic acid DMF solution was reacted for 3.5 hours, then cooled to 70°C, the remaining 0.0009g of dibutyltin dilaurate and 0.0002g of p-methylphenol were added, stirred for 20 minutes, and then 4.5g of polysiloxane was added and stirred for 5 hours, then cooled to 50°C, 0.015mol of triethylamine and 7.5mL of deionized water were added, and stirred at 1200rpm for 20 minutes to obtain modified polyurethane acrylate. The functional monomer DMF solution was prepared by mixing and stirring the functional monomer and DMF in a dosage ratio of 3g:10mL, and the 2,2-dihydroxymethylpropionic acid DMF solution was prepared by mixing and stirring 2,2-dihydroxymethylpropionic acid and DMF in a dosage ratio of 2g:10mL.

[0017] The modified nanocellulose is prepared by the following steps: 2 g of nanocellulose was ground for 2 h, and then 50 mL of DMF was added and mixed evenly, 3.5 g of 4-bromo-1-butene and 2.5 g of sodium hydroxide were added, and the mixture was stirred for 17 h. The mixture was centrifuged and purified to obtain modified nanocellulose.

[0018] Example 3: Polysiloxane is synthesized by the following steps: 0.005 mol of trifluoropropane trimethoxysilane, 0.01 mol of dimethyldimethoxysilane, 0.003 mol of diphenylsilanediol, 0.002 mol of pentaerythritol triacrylate and 0.07 g of barium hydroxide are mixed and stirred evenly, and nitrogen is continuously introduced, the temperature is raised to 85°C for reaction for 6 hours, and vacuum dried to obtain polysiloxane.

[0019] The modified polyurethane acrylate is prepared by the following steps: Step A1, 0.02 mol 1,3-dibromopropane and 2.5 g sodium hydroxide were evenly dispersed in 100 mL N,N-dimethylformamide (DMF), and then 0.068 mol diethanolamine was added, and the mixture was stirred at room temperature for 24 hours, and purified to obtain an intermediate; Step A2, disperse 0.03 mol of epichlorohydrin in 100 mL of methanol, transfer to an oil bath, and heat to 70° C., then slowly add 15.5 g of the intermediate and stir to react for 7 h, cool to room temperature, distill under reduced pressure, and wash to obtain a functional monomer; Step A3: Mix 0.03 mol polyethylene adipate (molecular weight 1000) and 0.0048 g dibutyltin dilaurate after vacuum drying and dehydration, stir for 10 min at 60 °C under nitrogen, slowly add 0.07 mol isophorone diisocyanate and stir for 60 min, then heat to 85 °C, add 10 mL functional monomer DMF solution, stir for 2.5 h, and then add 10 mL The 2,2-dihydroxymethylpropionic acid DMF solution was reacted for 4 hours, then cooled to 70°C, the remaining 0.0012g of dibutyltin dilaurate and 0.0003g of p-methylphenol were added, stirred for 30 minutes, and then 6g of polysiloxane was added and stirred for 6 hours, then cooled to 55°C, 0.26mol of triethylamine and 10mL of deionized water were added, and stirred at 1500rpm for 20 minutes to obtain modified polyurethane acrylate. The functional monomer DMF solution was prepared by mixing and stirring the functional monomer and DMF in a dosage ratio of 4g:10mL, and the 2,2-dihydroxymethylpropionic acid DMF solution was prepared by mixing and stirring 2,2-dihydroxymethylpropionic acid and DMF in a dosage ratio of 2.5g:10mL.

[0020] The modified nanocellulose is prepared by the following steps: 3 g of nanocellulose was ground for 3 h, and then 50 mL of DMF was added and mixed evenly, 4 g of 4-bromo-1-butene and 3.5 g of sodium hydroxide were added, and the mixture was stirred for 20 h. The mixture was centrifuged and purified to obtain modified nanocellulose.

[0021] Embodiment 4: A method for preparing a water-based UV coating comprises the following steps: 35 parts of acrylic resin, 20 parts of modified polyurethane acrylate prepared in Example 1, 1 part of modified nanocellulose prepared in Example 1, 4 parts of photoinitiator TPO, 0.1 parts of Tego810 defoamer, 0.3 parts of diacetone alcohol, and 15 parts of deionized water; The raw materials were weighed by weight, and the acrylic resin, the modified polyurethane acrylate prepared in Example 1 and deionized water were mixed and stirred, and then the modified nanocellulose prepared in Example 1, the photoinitiator TPO, and the Tego810 defoaming agent were added and mixed and stirred for 10 minutes, and then ultrasonically treated for 30 minutes to obtain a water-based UV coating.

[0022] Embodiment 5: A method for preparing a water-based UV coating comprises the following steps: 40 parts of acrylic resin, 25 parts of modified polyurethane acrylate prepared in Example 2, 2 parts of modified nanocellulose prepared in Example 2, 5 parts of photoinitiator TPO, 0.3 parts of Tego810 defoamer, 0.4 parts of diacetone alcohol, and 20 parts of deionized water; The raw materials were weighed by weight, and the acrylic resin, the modified polyurethane acrylate prepared in Example 2 and deionized water were mixed and stirred, and then the modified nanocellulose prepared in Example 2, the photoinitiator TPO, and the Tego810 defoaming agent were added and mixed and stirred for 15 minutes, and then ultrasonically treated for 30 minutes to obtain a water-based UV coating.

[0023] Embodiment 6: A method for preparing a water-based UV coating comprises the following steps: 45 parts of acrylic resin, 30 parts of modified polyurethane acrylate prepared in Example 3, 3 parts of modified nanocellulose prepared in Example 3, 6 parts of photoinitiator TPO, 0.5 parts of Tego810 defoamer, 0.5 parts of diacetone alcohol, and 25 parts of deionized water; The raw materials were weighed by weight, and the acrylic resin, the modified polyurethane acrylate prepared in Example 3 and deionized water were mixed and stirred, and then the modified nanocellulose prepared in Example 3, the photoinitiator TPO, and the Tego810 defoaming agent were added and mixed and stirred for 20 minutes, and then ultrasonically treated for 30 minutes to obtain a water-based UV coating.

[0024] Comparative Example 1: This comparative example is a water-based UV coating. The difference from Example 6 is that commercially available polyurethane acrylate is used instead of the modified polyurethane acrylate prepared in Example 3, and the rest is the same.

[0025] Comparative Example 2: This comparative example is a water-based UV coating. The difference from Example 6 is that nanocellulose is used instead of the modified nanocellulose prepared in Example 3, and the rest is the same.

[0026] The water-based UV coatings prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests: Adhesion test: according to the national standard "GB9286-88 Cross-cut test for paint and varnish film"; Water resistance test: The obtained water-based UV coating was coated on a wooden board with a coating thickness of 30 μm, and then the substrate was placed under a UV lamp for irradiation. After the coating was cured, a paint film was obtained. The wooden board was immersed in pure water at 25°C, and the bubbling time of the paint film was recorded. The shorter the time, the worse the water resistance of the paint film. Abrasion resistance test: Refer to GB / T1768-2006 Determination of abrasion resistance of paints and varnishes, rotating rubber grinding wheel method, speed 100r; Antibacterial performance test: GB / T 21866-2008 Antibacterial coating (paint film) antibacterial property determination method and antibacterial effect, wood board is used for coating sample preparation; The test results are shown in Table 1: Table 1: Performance test results

[0027] As can be seen from Table 1, after the adhesion, wear resistance, water resistance and antibacterial performance tests of the water-based UV coating prepared by the present invention, the adhesion grade is 1, the water resistance time is in the range of 210h-225h, the wear resistance is in the range of 0.022g-0.025g, and the antibacterial rate is greater than 99%, indicating that the coating film formed after the water-based UV coating is cured has excellent adhesion, wear resistance, water resistance and antibacterial properties.

[0028] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A water-based UV coating, characterized in that: The invention comprises the following raw materials in parts by weight: 35-45 parts of acrylic resin, 20-30 parts of modified polyurethane acrylate, 1-3 parts of modified nanocellulose, 4-6 parts of photoinitiator, 0.1-0.5 parts of defoamer, 0.3-0.5 parts of leveling agent and 15-25 parts of deionized water; The modified polyurethane acrylate is prepared by the following steps: Step A1, 1,3-dibromopropane and sodium hydroxide are uniformly dispersed in N,N-dimethylformamide, and diethanolamine is added, and the mixture is stirred at room temperature for 24 hours, and purified to obtain an intermediate; Step A2, dispersing epichlorohydrin in methanol, transferring to an oil bath, and heating to 60-70° C., then slowly adding the intermediate and stirring to react for 5-7 hours, cooling to room temperature, and distilling and washing under reduced pressure to obtain a functional monomer; Step A3, the vacuum dried and dehydrated polyethylene adipate and 80% dibutyltin dilaurate are mixed, stirred at 50-60° C. under nitrogen for 10 min, isophorone diisocyanate is slowly added and stirred for 30-60 min, then the temperature is raised to 75-85° C., a functional monomer DMF solution is added, the mixture is stirred for 1.5-2.5 h, 2,2-dihydroxymethylpropionic acid DMF solution is added and the mixture is reacted for 3-4 h, then the temperature is lowered to 70° C., the remaining 20% ​​dibutyltin dilaurate and p-methylphenol are added, the mixture is stirred for 10-30 min, polysiloxane is added and the mixture is stirred for 4-6 h, then the temperature is lowered to 45-55° C., triethylamine and deionized water are added, and the mixture is stirred at a speed of 1000-1500 rpm for 20 min to obtain modified polyurethane acrylate.

2. A water-based UV coating according to claim 1, characterized in that: In step A1, the usage ratio of 1,3-dibromopropane, sodium hydroxide, N,N-dimethylformamide and diethanolamine is 0.01-0.02 mol: 1.25-2.5 g: 100 mL: 0.034-0.068 mol.

3. A water-based UV coating according to claim 1, characterized in that: The usage ratio of epichlorohydrin, methanol and intermediate in step A2 is 0.01-0.03 mol:100 mL:5.25-15.5 g.

4. A water-based UV coating according to claim 1, characterized in that: In step A3, the dosage ratio of polyethylene adipate, dibutyltin dilaurate, isophorone diisocyanate, functional monomer DMF solution, 2,2-dihydroxymethylpropionic acid DMF solution, p-methylphenol, polysiloxane, triethylamine and deionized water is 0.02-0.03 mol: 0.003-0.006 g: 0.05-0.07 mol: 10 mL: 10 mL: 0.0001-0.0003 g: 3-6 g: 0.01-0.26 mol: 5-10 mL.

5. A water-based UV coating according to claim 4, characterized in that: In step A3, the functional monomer DMF solution is prepared by mixing and stirring the functional monomer and DMF in a dosage ratio of 2-4 g:10 mL, and the 2,2-dihydroxymethylpropionic acid DMF solution is prepared by mixing and stirring 2,2-dihydroxymethylpropionic acid and DMF in a dosage ratio of 1.5-2.5 g:10 mL.

6. A water-based UV coating according to claim 4, characterized in that: In step A3, the polysiloxane is synthesized by the following steps: trifluoropropane trimethoxysilane, dimethyl dimethoxysilane, diphenylsilane diol, pentaerythritol triacrylate and barium hydroxide are mixed and stirred evenly, and nitrogen is continuously introduced, the temperature is raised to 75-85° C., the reaction is carried out for 5-6 hours, and vacuum drying is performed to obtain polysiloxane.

7. A water-based UV coating according to claim 6, characterized in that: The usage ratio of trifluoropropane trimethoxysilane, dimethyl dimethoxysilane, diphenylsilane diol, pentaerythritol triacrylate and barium hydroxide in the polysiloxane is 0.001-0.005 mol: 0.005-0.01 mol: 0.001-0.003 mol: 0.001-0.002 mol: 0.04-0.07 g.

8. A water-based UV coating according to claim 1, characterized in that: The modified nanocellulose is prepared by the following steps: grinding the nanocellulose for 1-3 hours, adding DMF and stirring evenly, adding 4-bromo-1-butene and sodium hydroxide, stirring and reacting for 15-20 hours, centrifuging and purifying to obtain the modified nanocellulose.

9. A water-based UV coating according to claim 8, characterized in that: The dosage ratio of nanocellulose, DMF, 4-bromo-1-butene and sodium hydroxide in the modified nanocellulose is 1-3 g: 50 mL: 3-4 g: 1.5-3.5 g.

10. A method for preparing the water-based UV coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh the raw materials by weight, mix the acrylic resin, modified polyurethane acrylate and deionized water, stir and mix them evenly, then add the modified nanocellulose, photoinitiator, defoamer and leveling agent, stir and mix for 10-20 minutes, and then ultrasonically treat for 30 minutes to obtain the water-based UV coating.